Organizational Structure and Public Service Satisfaction in Yogyakarta City - PRIBADI, ULUNG (Jurnal Studi Pemerintahan, 2013)
This research aims at explaining the relation betweenorganizational structure and public service satisfaction.The survey is conducted technically by requestingsome respondents to grade the implementationof changes in organizational structure and performanceof Licensing Department of Yogyakarta, Indonesia.The academic findings are: (1) the implementationof the policy of changes in organizationalstructure led to the characteristics of post-bureaucraticorganization, (2) the public service satisfactionhas been in the relatively high level, and (3) therelationship between organizational structure andpublic service satisfaction is positive and significant.The theoretical implication of this research is thatthe empirical study supports the assumption whichthe organizational structure affects public services.The practical implication that could be recommendedis that the characteristics of organizational structureshould be fostered. Thus, the citizens obtaining servicesfrom the institution would be very satisfied. Thelimitation of this research is the small population ofsamples and respondents so that it would be hardto generalize the findings. It is suggested that theexplanation of why public organization could provideaccess and assurance for citizens in lower levelcould be the issues to be investigated further.KEYWORDS: Public Service, Organizational Structure,Institution, Citizen, Assurance